Antibacterial and phytochemical screening of Anethum graveolens, Foeniculum vulgare and Trachyspermum ammi - Arora Daljit S; Kaur Gurinder J (BMC, 2009)
Abstract Background Anethum graveolens Linn., Foeniculum vulgare Mill. and Trachyspermum ammi L. are widely used traditional medicinal plants to treat various ailments. To provide a scientific basis to traditional uses of these plants, their aqueous and organic seed extracts, as well as isolated phytoconstituents were evaluated for their antibacterial potential. Methods Antibacterial activity of aqueous and organic seed extracts was assessed using agar diffusion assay, minimum inhibitory concentration and viable cell count studies; and their antibacterial effect was compared with some standard antibiotics. The presence of major phytoconstituents was detected qualitatively and quantitatively. The isolated phytoconstituents were subjected to disc diffusion assay to ascertain their antibacterial effect. Results Hot water and acetone seed extracts showed considerably good antibacterial activity against all the bacteria except Klebsiella pneumoniae and one strain of Pseudomonas aeruginosa. Minimum inhibitory concentration for aqueous and acetone seed extracts ranged from 20-80 mg/ml and 5-15 mg/ml respectively. Viable cell count studies revealed the bactericidal nature of the seed extracts. Statistical analysis proved the better/equal efficacy of some of these seed extracts as compared to standard antibiotics. Phytochemical analysis showed the presence of 2.80 - 4.23% alkaloids, 8.58 - 15.06% flavonoids, 19.71 - 27.77% tannins, 0.55-0.70% saponins and cardiac glycosides. Conclusion Antibacterial efficacy shown by these plants provides a scientific basis and thus, validates their traditional uses as homemade remedies. Isolation and purification of different phytochemicals may further yield significant antibacterial agents.